Rethinking religious education and plurality : issues in diversity and pedagogy - Jackson, Robert, 1945- (RoutledgeFalmer, 2004)
Religions and Education is an argument for a plural as opposed to a secular, approach to education - an approach that accomodates and celebrates religious and cultural diversity and seeks to equip students with a sound and sympathetic knowledge.